The things we never say : a novel - Strout, Elizabeth (Random House, 2026)
"Artie Dam is a man with a secret. He goes about his days teaching American history to high schoolers, correcting their casual ignorance, and lending a kind word to those who need it most. He spends his free time sailing the beautiful Massachusetts Bay, or with his adult son and his wife of more than three decades - and as Artie does these things, he plans the event that will forever change the world he inhabits. But when a startling accident awakens a new perspective in Artie, and he realizes that life has its own secret it's been keeping from him - along with a lot more to say on the weighty matters of fate and freedom in his home and his country - he charts another course full of grief, hilarity, and heart, to a place where the end marks the beginning. Elizabeth Strout, as we have come to expect, delivers a profound exploration of the human condition - one that brims with deep compassion for each and every one of her characters. With exquisite prose and gentle intimacy, Artie Dam takes one man's fears and loneliness and makes them universal. And in the same breath, captures the mysterious love that sustains and holds us through it all"-- Provided by publisher.